Pengaruh Model Cooperative Learning Tipe Make a Match terhadap Hasil Belajar Matematika Siswa Kelas IV SD Kelurahan Pejaten Barat Jakarta Selatan 2014 - Sella Oktaviana (Neolectura, 2022)
The research aimed analyzed the effect of Cooperative Learning Tipe Make a Match model can influence the mathematics outcomes of fourth grade students in Pejaten Barat district Jakarta Selatan. The research method which use on this research was experimental method. The research design is true experimental design. The population of the research is all of the fourth grade students in Pejaten Barat district South Jakarta , whereas the sample technique of this research is cluster random sampling technique. From the lottery, it was chosen 40 students from SDN Pejaten Barat 01 which in experiment group and 40 students from SDN Pejaten Barat 03 in control group. The collecting of the data research was do by hypothesis`test using t-test. The outcomes of the research shows Cooperative Learning Tipe Make a Match model that has the significant effect for the mathematics learning outcomes of fourth grade students on district Pejaten Barat Jakarta Selatan. Because of that, the school needs to develop the proper approach of teaching and learning for the certain subject to give the positive effect for students mathematics learning outcomes. So, the purpose of learning can be reach.